Quality of life, sexual satisfaction, anxiety and depression status in lymphoma survivors - Serife Solmaz; Tugba Cetintepe; Dogus Turkyilmaz; Nuri Asik; Fatih Demirkan; Mehmet Ali Ozcan; Hayri Guner Ozsan; Bulent Undar; Oktay Bilgir; Ahmet Alacacioglu; Inci Alacacioglu (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2022)
Objective: The progressive development of lymphoma therapies has led to an important prolongation of patient survival. We aimed to investigate anxiety, depression, sexual satisfaction and health-related quality of life status in these lymphoma survivors. We examined the effects of depression, anxiety and sexual satisfaction on the quality of life. Materials and methods: In a prospective study, the data were collected from fifty lymphoma survivors. We used six forms. These forms consist of sociodemographic features, the Beck Depression Inventory (BDI), Beck Hopelessness Scala (BHS), State-Trait Anxiety Inventory (STAI I-II), Golombock-Rust Inventory of Sexual Satisfaction (GRISS) and European Organization for Research on the treatment of Cancer Questionnaires Quality of Life (QoL) - C30 questionnaires. Results: The mean age of the patients was 50,2 ± 14,8 (20 - 75) years, and 50% of them were females. In our study, we found that 26% of the patients had high depression values above the cutoff (≥ 17 of BDI score). The mean depression score of the patients was 10,6 ± 8 (0 - 32) and the mean hopelessness score was 5,7 ± 4,5 (0 - 19). The patients whose anxiety and depression scores were high role, cognitive and emotional functioning of EORTC-QLQ-C30 was found statistically significantly low. The mean STAI-I score of the patients was 35,6 ± 11,3 (22-73) and the mean STAI-II score was 41,4 ± 10,6 (23 - 67). Statistical significance in terms of emotional and social functioning was found in the patients with high anxiety scores. When all patients were evaluated with respect to GRISS, we found high scores (> 5) for frequency, communication, vaginusmus and premature ejaculation. We compared the EORTC-QoL-C30 scores and GRISS of the patients. There was an association between emotional dysfunction with high scores of frequency (p = 0.040). Also, there was an association between low scores of role functioning with high scores of avoidance and premature ejaculation (p = 0.015, p = 0.003). However, there was a significant correlation between low scores of global QoL with high scores of avoidance, communication, and touch. There was no statistically significant difference between the anxiety and depression levels of the patient according to gender. But, some functional scales including role function (p = 0.001), social function (p = 0.001) and cognitive function (p = 0.027) were lower in female patients. Conclusion: The lymphoma survivors had high anxiety and depression scores, reduced sexual functioning and low functioning scales of QoL. There was an association between sexual dysfunction low role, emotional functioning and global QoL scores in patients.